The effect of build direction and geometric optimization in laser powder bed fusion of Inconel 718 structures with internal channels. (September 2021) - Kasperovich, Galina; Becker, Ralf; Artzt, Katia; Barriobero-Vila, Pere; Requena, Guillermo; Haubrich, Jan
Graphical abstract: Highlights: Significant improvement in dimensional accuracy of Inconel 718 thin channels produced by laser powder fusion (LPBF) through a multi-component optimization is achieved. Roughness of flat surfaces tilted at 0°, 45°, 90° and 135° to the working platform is optimized. Build direction effect on the quality of inclined shaped channels is analysed using computed tomography. Optimized LPBF contour parameters in combination with modified channel shapes allowed nearly ideally round channels in all building orientations for design of combustion chambers for future aircraft engines. Abstract: A laser powder bed fusion (LPBF) strategy was developed for manufacturing small channels with high dimensional accuracy in Inconel 718 structures. Particular attention was paid to surface characteristics such as equivalent diameter and shape factor. The inherent surface quality of external surfaces was optimized by a systematic variation of the LPBF contour parameters as well as the channel cross-section. The mean arithmetic roughness Sa was analysed for upskin, vertical and downskin surfaces with respect to the build platform. Simultaneously, the effect of the build direction on the quality of internal free-shaped surfaces was investigated on channels with diameters from 500 to 1000 µm and build orientations from the horizontal (0°) to vertical (90°). A significant improvement in dimensional accuracy was achieved by using an optimized droplet-shaped cross-section that is scaled as a function with the build inclination. An angular analysis of the surface roughness in different regions of the channels confirms that this modified cross-section reduces the fraction of channel regions that show a particularly high surface roughness due to inward melting. In combination with an optimized contour processing strategy, the modified channel resulted in the best properties for inclinations below 45°. The shape factor increased from 0.4 to almost 0.9, i.e., close to the ideally round shape.